The impact of digital accounting on the quality and transparency of information presented by organizations using ERP systems. Opportunities for Cloud ERP Vs. On-premise ERP - Laura-Eugenia-Lavinia Barna (Revista de Studii Financiare, 2021)
The rapid progress of IT technologies in recent years was favored by the emergence of the phenomenon of digitalization, especially in the field of accounting. The purpose of the legislation and standards is to accord support for continuous development of both IT technologies and the organization. The main objective of this paper is to observe the manner in which the digitalization of accounting influences the quality and transparency of information if employees use ERP systems. In order to study the role and opportunities offered by ERP systems on accounting, the author used a study based on the review of the literature, but also on the analysis of the results obtained using the constructed questionnaire. The results show that ERP systems have a positive effect on the digitalization process and most respondents believe that an ERP system on a Cloud server is considered much more efficient and secure than an ERP system based on a local server (on-premise).